Clinical linguistics: Conversational reflections. (April 2013) - Crystal, David
<x xml:space="preserve">Abstract</x> This is a report of the main points I made in an informal "conversation" with Paul Fletcher and the audience at the 14th ICPLA conference in Cork. The observations arose randomly, as part of an unstructured 1-h Q&A, so they do not provide a systematic account of the subject, but simply reflect the issues which were raised by the conference participants during that time.